KAJIAN STILISTIKA PADA YOUTUBE “ATAP NEGERI PAPUA TENGAH” - Faqih Fathkurullah Arrahman; Sugit Zulianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is inspired by the phenomenon of esthetic and captivating language use in audiovisual content, particularly in the works of Fiersa Besari, which are often enjoyed visually without a deep understanding of their linguistic construction. Therefore, this research aims to describe the use of diction, language style, and imagery in the oral narration of the YouTube video